PENGARUH CORPORATE GOVERNANCE INDEX, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP BIAYA UTANG (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2017) - Ika Erniawati; Nur Hidayati; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the effect of corporate governance index, institutional ownership and managerial ownership on the cost of debt. This research is quantitative research, sample selection is done by purposive sampling method with a sample of 25 companies listed on the Indonesia Stock Exchange 2015-2017. The analysis technique used to test the hypothesis formulated in this study is multiple regression analysis. The results of this study indicate that the corporate governance index has a t-count value of -3,645 and a significance value of 0,000 <0,05. This test shows that H0 is rejected and Ha is accepted. So that it can be concluded that corporate governance index (X1) has an effect on variable Y (cost of debt). Institutional ownership has a t-count value of -2.413 and a significance value of 0.016 <0.05. This test shows that H0 is rejected and Ha is accepted. So that it can be concluded that institutional ownership affects the cost of debt.Keywords: Corporate Governance Index, Institutional Ownership, Managerial Ownership, Debt Costs